The Burden of Noncommunicable Diseases in Ethiopia, 2000–2016: Analysis of Evidence from Global Burden of Disease Study 2016 and Global Health Estimates 2016. (20th February 2020) - Girum, Tadele; Mesfin, Dereje; Bedewi, Jemal; Shewangizaw, Misgun
Abstract : Background . The continuing rise in the burden of noncommunicable diseases (NCDs) is a key global health agendum due to the fact that NCDs cause more deaths than all other causes combined together. Although measuring the burden of NCD is very important to improve the existing health care systems and to monitor the progress of the program, a comprehensive estimate is lacking in Ethiopia. Hence, we aimed to systematically analyze the existing evidence to bring a solution. Methods . The research used data from the Global Burden of Disease Study (GBD 2016) and Global Health Estimates 2016 that originally collected the information through vital registration, verbal autopsy, surveys, reports, and modeling. Results . In 2016, NCD caused an estimated 274998.8 (95% CI: 211290.2–362882.1) deaths among all ages and both genders with a crude death rate of 268.5/100000 and age-standardized death rate (ASDR) of 554.7/100000 population. It contributed to 39.3% of the total death, 53% of ASDR, and 34% of DALYs. The number of deaths and DALYs from NCD has increased by 38% and 31.5%, respectively, whereas CDR and ASDR from NCD have declined by 10.3% and 12.5%, respectively. Cardiovascular diseases, malignant neoplasms, digestive diseases, respiratory diseases, diabetes mellitus, and neurological conditions were the leading level 2 causes of ASDR due to NCD, while ischemic heart disease, stroke, other circulatory diseases, cirrhosis of the liver, and COPD were the top 5 causes of ASDR from NCD at level 3 causes. Conclusion and Recommendation . The burden of NCD was remarkably increased between 2000 and 2016. It carries the highest burden of ASDR. Cardiovascular diseases and malignant neoplasms were the two most common causes of mortality and DALYs. Therefore, the existing disease prevention strategies should be strengthened by incorporating strategies addressing noncommunicable diseases.